The Relationship between the Classroom Management and Student Quality in Schools - Sriboonrueng, Apinya; Areerat, Wanllapa (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Classroom Management is a teaching behavior of teachers to help teaching efficiency. By promoting the atmosphere in the classroom, the use of technology in teaching and learning management, and organizing activities suitable for each learner to develop quality learners. The objectives of this research were 1) Classroom Management 2) Student Quality and 3) relationship between the Classroom Management and Student Quality in schools. Methodology: The samples were 330 administrators and teachers. The instrument used for data collection was a questionnaire that has a reliability level of 0.983. The statistics used in the data analysis were percentage, mean, standard deviation, and Pearson’s Correlation Coefficient Test. Results: The research results revealed that: 1) Classroom Management indicated a high level. The highest mean was providing a safe atmosphere and environment and supervision, following up and developing teachers in the professional community and the lowest mean was bringing change to quality classrooms. 2) The Student Quality in schools indicated a high level. The highest mean was social skills and the aspect with the lowest mean was learning process skills. And 3) The relationship between Classroom Management and Student Quality in schools. There was a high correlation (r = 0.765) with statistical significance at the 0.01 level. Conclusion: The results of the study on classroom management showed that there was a high average across all areas focusing on atmosphere and supervision. However, bringing change to classroom quality had the lowest average. Overall learner quality is average, with social skills being the highest and learning process skills being the lowest. And there is a high relationship between classroom management and student quality.